Maxigrain® enzyme supplementation effect on serological indices of African catfish Clarias gariepinus (Burchell, 1822) fed Gliricidia sepium(Jacq.) leaf meal - Ogungbesan, AM; Akanj, AM; Sule, SO; Oyetunji, TA; Eniolorunda, OO (Bangladesh Journal of Animal Science, 2020)
A total of 50 African catfish (Clarias gariepinus) juvenile with average weight 208 ± 6g serum indices were used to monitor the effect of levels of Maxigrain in catfish fed Gliricidia sepium leaf meal. Five experimental diets were formulated which is ascribe to T1, T2, T3, T4 and T5 at 0, 5, 10, 15, and 20% Maxigrain supplemented with 10% Gliricidia sepium. Although results showed that after twelve (12) weeks of feeding, fish fed with 15% Maxigrain (T4) supplemented with 10% G. sepium leaf meal gave the best response in terms of the variables monitored, all the parameters were within the normal physiological range. Hence catfish can be fed with plant protein sources with enzyme supplementation while still maintain their normal health status. Bang. J. Anim. Sci. 2020. 49 (1): 37-44